Pediatric surgical specialty in India: Sunset or in an eclipse? Current status: 2014-15 - Raghunath, B V; Murthy, M Keshav; Girish, M L (Indian Journal of Child Health, 2016)
Background: Pediatric surgical specialty in India is more than 50-year-old. In spite of the advances made in pediatric surgical care, the specialty is still not being recognized as a “super specialty” and given importance in par with other super specialties. There is a decrease in the demand for pediatric surgical trainee posts. Aims: To assess the current status of pediatric surgical services in India and analyze the factors contributing to decrease in demand for pediatric surgical trainee posts. Materials and Methods: A web-based survey was conducted in January 2014. A questionnaire was sent to all members of Indian Association of Pediatric Surgeons via e-mail and the results were analyzed. Survey Monkey statistical software was used for analysis of data. Results: A total of 145 (24.5%) members responded to the survey. The majority of the members were practicing in metros and were dissatisfied because of the lesser remuneration as compared to other super specialties. However, the majority of the members were happy socially and professionally and expected a bright future for the specialty. Conclusion: Pediatric surgery, like any other surgical branch, has short comings. Pediatric surgical specialty in India is currently in an eclipse rather than in a sunset.